2021
DOI: 10.25115/eea.v39i11.5842
|View full text |Cite
|
Sign up to set email alerts
|

A comparative Study in the Role of Private Sector in Relationships Analysis between Economic Sustainability and COVID-19: Evidence from Iraq and Russia

Abstract: The study is designed to investigate the effect of the twin crisis on the private sector and national outlook of the oil dependent nations of Iraq and Russia. It is specifically aimed to evaluate and compare the recovery strategies put in place to survive the small and medium size enterprise. It is also of specific concern to estimate the end to pressure on this sector resulting from the global health problem. Descriptive and comparative research methods forms the central analytical tools employed to synthesis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 14 publications
(16 reference statements)
0
4
0
Order By: Relevance
“…According to the World Tourism Council, this revenue was estimated at (5) billion dollars in 2017, but it was the sector most affected by the pandemic. It includes the owners of hotels and restaurants whose sales depend on tourists, as well as recreational tourism and archaeological sites, which represent 25% of the country's tourism revenues, which are in the northern side of Iraq after the virus stopped the movement of the entire world (Altameemi & Flayyih, 2021).…”
Section: Tourism Sectormentioning
confidence: 99%
“…According to the World Tourism Council, this revenue was estimated at (5) billion dollars in 2017, but it was the sector most affected by the pandemic. It includes the owners of hotels and restaurants whose sales depend on tourists, as well as recreational tourism and archaeological sites, which represent 25% of the country's tourism revenues, which are in the northern side of Iraq after the virus stopped the movement of the entire world (Altameemi & Flayyih, 2021).…”
Section: Tourism Sectormentioning
confidence: 99%
“…The study results revealed that reduced transportation consumption affects China's macro-economy and decreases all industrial sectors' output. Furthermore, the service sector is the most The decline in economic growth during the COVID-19 pandemic has highlighted the need for other sectors, such as NGOs, researchers, and communities, to play a role in the post-pandemic recovery [11,38,39]. Although some stakeholders sometimes have different perceptions regarding the handling of the COVID-19 pandemic, they are classified into three main groups, namely, those who respond positively, in a negative way and neutrally [40].…”
Section: Introductionmentioning
confidence: 99%
“…In 2020, the economic growth rate declined to -2.28%, a sharp drop from 6.79% in the previous year (Figure 2). The decline in economic growth during the COVID-19 pandemic has highlighted the need for other sectors, such as NGOs, researchers, and communities, to play a role in post-pandemic recovery [11,37,38]. Although some stakeholders sometimes have different perceptions regarding the handling of the Covid-19 pandemic [39].…”
Section: Introductionmentioning
confidence: 99%